Ancient Greece - Terzi, Marinella (Chicago : Childrens Press, 1992)
Discusses the culture of ancient Greece and examines the temples, statues, and other physical remains of that time.
Includes index.
Translation of: La antigua Grecia.
School Library Journal.
6.1
5-8
Keywords: Greece -- Civilization -- To 146 B.C. -- Juvenile literature; Greece -- Antiquities; Greece -- Civilization -- To 146 B.C.; Greece -- Antiquities; Greece -- Civilization